MENGEMBANGKAN KETERAMPILAN MEMBACA DAN MENULIS ANAK DESA MELALUI KEGIATAN GUBUK LITERASI DI DESA SUKOLILO KECAMATAN JABUNG KABUPATEN MALANG JAWA TIMUR - Intan Qonita Fransisca; Septina Lisdayanti (Bajang Institute, 2023)
Contribution is all involvement that is given by certain individuals or bodies which then position their roles, so that they can have certain impacts that can be assessed from social and economic aspects. Every individual and group contributes, so you give something-whether it's your money, possessions, or your time. Contributions can be made in various forms, some are measurable, for example when you donate a certain amount of money to build a mosque in your neighborhood, but there are also contributions that are not very tangible or cannot be counted, for example when a student raises his hand in class to ask a question, he contributed, as the answers to his questions enriched the learning experiences of other students. In developing reading and writing skills, an activity is needed to develop these skills. One of the programs that can develop reading and writing skills is the village literacy hut activity. Through this literacy activity it can be seen that village children have relatively low reading and writing skills, so it is necessary to have sustainable and continuous activities from this village literacy hut activity so that village children's reading and writing skills continue to develop and are maintained